The Women Dresses Design Identity of TaiDam NaPa Nad Chiang Kan Loei Province - ชัยกุหลาบ อิสริยาภรณ์; สุดสังข์ นิรัช (Journal of Fine and Applied Arts Khon Kaen University, 2019)
The objective of this study were 1) to study of identity the dress of TaiDam NaPa Nad Chiang Kan Loei Province 2) to the Women Dresses Design Identity of TaiDam NaPa Nad and 3) to evaluation of satisfaction with for Women Dresses Design Identity of TaiDam NaPa Nad. This research is using tools such as questionnaires, in-depth interviews, and evaluation of satisfaction with for Women Dresses Design Identity of TaiDam NaPa Nad Chiang Kan Loei Province. The sample of 135 people, including community leaders, local scholars, designer fashion or art teachers 5 people, and tourists in Thailand and overseas, 80 villagers of TaiDam Na Pa Nad 50. The findings revealed that: 1) Today the women TaiDam Na Pa Nad most wear contemporary clothes. They wear ethnic dress for the job or the promotion of tourism. Respondents estimate that a female ideas that suit a particular ethnic group, she boldly striped pattern is woven of high-class women wear when they have important 2) The Women Dresses Design Identity of TaiDam NaPa Nad. The design principles are used to analyze the materials, the colors, the textures, patterns, and costumes, and 3) to evaluate the Women Dresses Design Identity of TaiDam NaPa Nad found to be appropriate by the high level ( =4.42).